Experimental and theoretical study of pressure oscillation of unstable steam-air jet condensation in water in a rectangular channel. (October 2019) - Yang, Xiaoping; Liu, Jiping; Fu, Pengfei; Chen, Nana; Wei, Jinjia
Highlights: Dynamics of unstable steam-air jet condensing in water flow was investigated. Effect of air content on interface and pressure oscillation was discussed. Interface and pressure oscillation became extremely violent at low air content. Pressure oscillation intensity decreased when air content exceeded a critical value. Abstract: Pressure oscillation occurs during the steam jet condensation in water, notably in unstable flow pattern region. Consequently, pressure oscillation may risk the thermal system. In this work, we introduce a method of reducing the pressure oscillation intensity by adding a small amount of air into steam in unstable flow pattern region. The effects of the air content on the unstable flow patterns and pressure oscillation characteristics were studied experimentally. Notably, the air layer showed a periodic accumulation-and-dispersion phenomenon around the steam–water interface. This phenomenon resulted in a periodic and dramatic fluctuation of the interface at a relatively low air mass fraction. When the air mass fraction increased to a critical value, the flow pattern became stable due to a sharp reduction in condensation rate. Accordingly, the pressure oscillation intensity increased and then dropped at the critical air mass fraction, showing a convex-shaped distribution. The air mass fraction should exceed the critical value if air is added into steam to reduce the pressure oscillation intensity. Otherwise, the air could lead to a much stronger pressure oscillation. A theoretical model for the critical air mass fraction was established and could predict the critical air mass fraction within a deviation of ±14%.